Progressive Multiple Sclerosis (Springer International Publishing, 2018)
This revised, updated second edition draws together the basic science, pathology, epidemiology and treatment possibilities in progressive multiple sclerosis. Each chapter addresses specific aspects of progressive multiple sclerosis providing an extensive review of the current literature and a discussion of the likely mechanisms of tissue injury relevant to the disease. New additions to the second edition include a description of clinical scales used to determine levels of disability; recent trials specifically directed at reducing disease progression; rehabilitation; and an in depth discussion of the similarities and differences between primary and secondary multiple sclerosis. The biological processes underlying disease progression are elucidated as are specific pathophysiological mechanisms. The basic science of axonal degeneration and the clinical understanding of progressive multiple sclerosis are discussed in the context of emerging and future therapies for disease progression as are trials which have been and will be conducted for progressive multiple sclerosis. An overview of biomarkers for the disease is included and existing symptomatic therapies for progressive multiple sclerosis are covered in detail. Progressive Multiple Sclerosis, Second Edition is ideal for both general neurologists and those with a specialist interest in multiple sclerosis. It will also be of interest to neurologists in training and other medical professionals treating this common disease.